A high-nickel cathode active material, a preparation method thereof, and applications thereof
By optimizing the chemical composition and preparation process of high-nickel positive electrode active materials, the lithium-nickel mixed discharge problem is solved, the high first-time Coulomb efficiency and capacity of lithium-ion batteries are achieved, and the battery performance is improved.
Patent Information
- Application Number
- CN202410264547.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-07
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2044-03-07
AI Technical Summary
The existing high-nickel positive electrode active materials are prone to lithium-nickel mixed discharge in lithium-ion batteries, resulting in poor battery efficiency and capacity, which cannot meet the needs of high energy density and cycle life.
By controlling the chemical composition and preparation process of high-nickel positive electrode active materials, the lithium-nickel mixing rate is reduced, the layered structure of the material is optimized, the core layer and cladding layer structure are adopted, and the appropriate sintering temperature and time are combined to form a stable layered structure to improve the migration efficiency of lithium ions.
It significantly improves the first Coulomb efficiency and capacity of lithium-ion batteries, and improves the cycle performance and life of the battery.
Smart Images

Figure CN118117075B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium - ion batteries, relates to a high - nickel cathode active material, and particularly relates to a high - nickel cathode active material, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium - ion batteries are widely used in energy - storage power systems such as portable electronic devices, power tools, special equipment, special aerospace, and hydraulic, thermal, wind, and solar power stations due to their advantages of high energy density, low self - discharge rate, no memory effect, wide operating temperature range, safe use, and environmental protection. However, current lithium - ion batteries still cannot meet people's requirements for charge - discharge efficiency, cycle life, and capacity.
[0003] As an important component of lithium - ion batteries, the cathode active material accounts for a large proportion in lithium - ion batteries, and its performance will greatly affect the performance of the battery. The specific capacity of high - nickel cathode materials can reach more than 200 mAh / g, which can effectively improve the energy density of lithium - ion batteries. However, during the sintering process of high - nickel cathode active materials, the ionic radii of lithium ions and nickel ions are similar, and they will occupy each other's positions, easily resulting in the phenomenon of lithium - nickel mixing, which causes the first - cycle efficiency and capacity of the battery to deteriorate.
[0004] Therefore, it is very necessary to develop a high - nickel cathode active material with high initial Coulomb efficiency and high capacity. Summary of the Invention
[0005] In view of the above - mentioned defects, the present invention provides a high - nickel cathode active material, which has a relatively high initial Coulomb efficiency and capacity.
[0006] The present invention provides a preparation method of a high - nickel cathode active material. The high - nickel cathode active material prepared by this preparation method has a relatively high initial Coulomb efficiency and capacity.
[0007] The present invention provides a positive electrode sheet, which includes the above - mentioned high - nickel cathode active material or the high - nickel cathode active material prepared by the above - mentioned preparation method. Applying this positive electrode sheet to a lithium - ion battery can effectively improve the capacity and initial Coulomb efficiency of the lithium - ion battery.
[0008] The present invention provides a lithium - ion battery, which includes the above - mentioned high - nickel cathode active material, or the high - nickel cathode active material prepared by the above - mentioned preparation method, or the above - mentioned positive electrode sheet. This lithium - ion battery has a relatively high initial Coulomb efficiency and capacity.
[0009] The present invention provides a high - nickel cathode active material, which includes the chemical composition shown in Formula 1,
[0010] Li a Nib Mn m Co n X c O2 formula 1
[0011] In formula 1, 0.95≤a≤1.05, 0.90≤b≤0.98, 0<c≤0.016, b+m+n=1, and X includes at least two of Zr, Ti, W, B, Sn, Ta, Al, Mo, Co, and Ce;
[0012] The lithium-nickel mixing ratio of the high-nickel positive electrode active material is 0.009 to 0.015;
[0013] In the X-ray diffraction pattern of the high-nickel positive electrode active material, c / a is 4.8 to 5.2;
[0014] In the X-ray diffraction pattern of the high nickel positive active material, the peak areas of the diffraction peaks at 2θ of 18.8±0.5° and 44.3±0.5° are respectively 1 (003) , I (104) , and I (003) / I (104) It is 1.8 to 2.4.
[0015] Furthermore, the high-nickel positive electrode active material includes a core layer and a coating layer covering at least a portion of the surface of the core layer; the core layer includes a first core layer and a second core layer covering at least a portion of the surface of the first core layer; the first core layer has a chemical composition of Formula 2, the second core layer has a chemical composition of Formula 3, and the coating layer has a chemical composition of Formula 4.
[0016] Li d Ni e Mn f Co g X 1 h O2 Formula 2
[0017] LiX 2 O2 formula 3
[0018] LiX 3 O2 formula 4
[0019] In formula 2, 0.95≤d≤1.05, 0.9≤e≤0.98, e+f+g=1, 0<h≤0.016, X 1 including at least two of Zr, Ti, W, B, Sn, Ta, and Ce;
[0020] In formula 3, X 2 Including at least one of Zr, Ti, W, B, Sn, Ta, Al, Mo, and Co;
[0021] In Formula 4, X 3 includes at least one of W, Al, B, and Co.
[0022] Furthermore, the first core layer further includes the F element; the mass percentage content of the F element in the first core layer is 0.01 to 0.045 wt%.
[0023] Furthermore, the high-nickel cathode active material includes secondary particles composed of primary particles;
[0024] The median particle size of the primary particles is 0.2 to 1 μm, and / or the median particle size of the high-nickel cathode active material is 0.7 to 1.5 μm.
[0025] Furthermore, the specific surface area of the high-nickel cathode active material is 0.9 to 5 m 2 / g, and / or the powder tap density of the high-nickel cathode active material is 3.1 to 3.4 g / cm 3 .
[0026] The present invention also provides a method for preparing a high-nickel cathode active material, including the following steps:
[0027] (1) Calcining the high-nickel cathode material precursor Ni x Co y Mn z (OH)2 at 400 to 600 °C for 1 to 5 h, and obtaining a first product with a median particle size D50 < 0.8 μm after grinding and crushing, where 0.90 ≤ x ≤ 0.98 and x + y + z = 1;
[0028] (2) Mixing the first product, a lithium source, and a dopant to obtain a first mixed raw material, and performing a first sintering in an oxygen atmosphere at a sintering temperature of 600 to 850 °C for 15 to 20 h to obtain a second product;
[0029] The molar ratio of lithium in the lithium source to the first product is 0.95 to 1.05;
[0030] The mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is (0.1 to 10):1000;
[0031] (3) Mixing the second product and a first coating agent and performing a second sintering in an oxygen atmosphere at a sintering temperature of 500 to 600 °C for 8 to 12 h to obtain a third product;
[0032] (4) Mixing the third product and a second coating agent and performing a third sintering in a protective atmosphere at a sintering temperature of 300 to 400 °C for 6 to 8 h to obtain the high-nickel cathode active material.
[0033] Further, the first mixed raw material further includes a fluorine source;
[0034] The mass ratio of the fluorine source to the theoretical generated mass of the high-nickel cathode active material is (1-10):10000.
[0035] Further, the heating rate during the first sintering process is 1-4 °C / min, and / or the heating rate during the second sintering process is 1-3 °C / min, and / or the heating rate during the third sintering process is 1-3 °C / min.
[0036] The present invention also provides a cathode sheet, which includes the high-nickel cathode active material described in any one of the above, or includes the high-nickel cathode active material prepared by the preparation method of the high-nickel cathode active material described in any one of the above.
[0037] The present invention also provides a lithium-ion battery, which includes the high-nickel cathode active material described in any one of the above, or includes the high-nickel cathode active material prepared by the preparation method of the high-nickel cathode active material described in any one of the above, or includes the cathode sheet described above.
[0038] The high-nickel cathode active material of the present invention has the chemical composition shown in Formula 1, and its lithium-nickel mixing rate is relatively low, being 0.009-0.015, which will not hinder the insertion and extraction of lithium ions; at the same time, in the X-ray diffraction pattern of the cathode active material, c / a is 4.8-5.2, I (003) / I (104) is 1.8-2.4, and the ratio is relatively large, so that the content of the layered structure in the high-nickel cathode material is relatively large, and further the number of lithium ions that can move freely inside the material increases. During the charge and discharge process, lithium ions can migrate smoothly, effectively improving the first Coulomb efficiency and capacity of the cathode active material. Description of the Drawings
[0039] Figure 1 It is the SEM diagram of the high-nickel cathode active material in Example 1 of the present invention;
[0040] Figure 2 It is the SEM diagram of the high-nickel cathode active material in Example 2 of the present invention;
[0041] Figure 3 It is the SEM diagram of the high-nickel cathode active material in Example 3 of the present invention;
[0042] Figure 4 It is the SEM diagram of the high-nickel cathode active material in Example 4 of the present invention. Detailed Embodiments
[0043] To make the objectives, technical solutions, and advantages of the present invention clearer, the following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the embodiments of the present invention. Apparently, the described embodiments are part of the embodiments of the present invention, rather than all of them. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts belong to the scope of protection of the present invention.
[0044] In the first aspect of the present invention, a high-nickel cathode active material is provided, including a chemical composition shown in Formula 1, Li a Ni b Mn m Co n X c O2 Formula 1
[0045] In Formula 1, 0.95 ≤ a ≤ 1.05, 0.90 ≤ b ≤ 0.98, 0 < c ≤ 0.016, b + m + n = 1, and X includes at least two of Zr, Ti, W, B, Sn, Ta, Al, Mo, Co, and Ce;
[0046] The lithium-nickel mixing ratio of the high-nickel cathode active material is 0.009 to 0.015;
[0047] In the X-ray diffraction pattern of the high-nickel cathode active material, c / a is 4.8 to 5.2;
[0048] In the X-ray diffraction pattern of the high-nickel cathode active material, the peak areas of the diffraction peaks at 2θ of 18.8 ± 0.5° and 44.3 ± 0.5° are I (003) , I (104) , and I (003) / I (104) is 1.8 to 2.4.
[0049] Specifically, the lithium-nickel mixing ratio of the high-nickel cathode active material can be tested by XRD testing; the c / a and I (003) / I (104) of the high-nickel cathode active material can be tested by XRD testing.
[0050] According to the above solution provided by the present invention, applying the high-nickel cathode active material to a lithium-ion battery can effectively improve the capacity and first Coulombic efficiency of the battery. The inventor analyzed this principle and believed that the reason might be that when the high-nickel cathode active material has the chemical composition shown in Formula 1, and the lithium-nickel mixing ratio, c / a, I (003) / I (104)When they are respectively within the above ranges, the layered structure can be stabilized, the lattice oxygen can be stabilized, and the rapid insertion and extraction of lithium ions can be realized, so that the lithium ions of the positive electrode active material can migrate smoothly during charge and discharge, effectively improving the first Coulomb efficiency and capacity of the lithium ion battery including the positive electrode active material. If the lithium-nickel mixing ratio is lower than 0.009 or c / a is lower than 4.8 or I (003) / I (104) is lower than 1.8, the capacity is low and the cycle performance deteriorates; if the lithium-nickel mixing ratio is higher than 0.015 in terms of capacity or c / a is higher than 5.2 or I (003) / I (104) is higher than 2.4, the structural stability is poor and the electrochemical performance deteriorates.
[0051] The present invention does not limit the method for realizing the lithium-nickel mixing ratio, c / a and I (003) / I (104) of the high-nickel positive electrode active material. For example, by controlling the addition amount of each raw material and the process parameters during the preparation process, the lithium-nickel mixing ratio, c / a and I (003) / I (104) can be made to be within the above ranges.
[0052] In a specific embodiment, the high-nickel positive electrode active material includes a core layer and a coating layer covering at least a part of the surface of the core layer; the core layer includes a first core layer and a second core layer covering at least a part of the surface of the first core layer; the first core layer has a chemical composition of Formula 2, the second core layer has a chemical composition of Formula 3, and the coating layer has a chemical composition of Formula 4,
[0053] Li d Ni e Mn f Co g X 1 h O2 Formula 2 -
[0054]
[0054] LiX 2 O2 Formula 3
[0055] LiX 3 O2 Formula 4
[0056] In Formula 2, 0.95 ≤ d ≤ 1.05, 0.9 ≤ e ≤ 0.98, e + f + g = 1, 0 < h ≤ 0.016, X 1 includes at least two of Zr, Ti, W, B, Sn, Ta, Ce;
[0057] In Formula 3, X 2 includes at least one of Zr, Ti, W, B, Sn, Ta, Al, Mo, Co;
[0058] In Formula 4, X 3It includes at least one of W, Al, B, and Co.
[0059] When the high-nickel cathode active material includes the above structure and the first core layer, the second core layer, and the coating layer have the above chemical compositions, not only can the lithium-ion battery including the cathode active material have a high capacity and a first Coulombic efficiency, but also the second core layer and the coating layer therein can play a physical isolation role. This isolation role mainly has two aspects: on the one hand, it can isolate the electrolyte from the first core layer to avoid side reactions between the electrolyte and the first core layer during charge and discharge; on the other hand, it can avoid the release of lattice oxygen in the cathode active material in the form of oxygen during charge and discharge and the reaction with the electrolyte, resulting in problems such as capacity attenuation and decline in cycle performance.
[0060] In a specific embodiment, the first core layer further includes F element; the mass percentage content of F element in the first core layer is 0.01 - 0.045 wt%. When the first core layer includes F element, F can replace part of O in the first core layer to form F-Ni bonds, F-Co bonds, and F-Mn bonds with greater bond energy, reducing the content of unstable lattice oxygen in the first core layer, thereby inhibiting the dissolution of metal ions Ni, Co, and Mn and improving the battery capacity and life; at the same time, the presence of F increases the energy barrier for lithium-nickel diffusion, further restricting the generation of lithium-nickel mixing phenomenon; when the mass percentage content of F element is within the above range, the content of unstable lattice oxygen in the first core layer can be further reduced, thereby further improving the battery capacity and life.
[0061] Specifically, the mass percentage content of F element in the first core layer can be tested by an inductively coupled plasma emission spectrometer.
[0062] In a specific embodiment, the high-nickel cathode active material includes secondary particles composed of primary particles; the median particle size of the primary particles is 0.2 - 1 μm, and / or the median particle size of the high-nickel cathode active material is 0.7 - 1.5 μm. Within this range, the capacity of the high-nickel cathode active material can be further improved.
[0063] In a specific embodiment, the specific surface area of the high-nickel cathode active material is 0.9 - 5 m 2 / g. Within this range, the specific surface area of the cathode active material is relatively high, and the surface area available for lithium-ion insertion is also correspondingly large, which can effectively improve the electrode reaction activity and make the battery have a high capacity; at the same time, the specific surface area is not too large, which can ensure that the lithium-ion battery has good cycle performance.
[0064] In a specific embodiment, the powder tap density of the high-nickel cathode active material is 3.1 - 3.4 g / cm 3Within this range, a lithium-ion battery including this positive electrode active material can have a relatively high capacity, while maximizing the capacity performance of this material.
[0065] The second aspect of the present invention provides a method for preparing a high-nickel positive electrode active material, including the following steps:
[0066] (1) Calcining the high-nickel positive electrode material precursor Ni x Co y Mn z (OH)2 at 400 - 600 °C for 1 - 5 h, and obtaining a first product with a median particle size D50 < 0.8 μm after grinding and crushing, where 0.90 ≤ x ≤ 0.98 and x + y + z = 1;
[0067] (2) Mixing the first product, a lithium source, and a dopant to obtain a first mixed raw material, and performing a first sintering in an oxygen atmosphere at a sintering temperature of 600 - 850 °C for 15 - 20 h to obtain a second product;
[0068] The molar ratio of lithium in the lithium source to the first product is 0.95 - 1.05;
[0069] The mass ratio of the dopant to the theoretical generated mass of the high-nickel positive electrode active material is (0.1 - 10):1000;
[0070] (3) Mixing the second product and a first coating agent and performing a second sintering in an oxygen atmosphere at a sintering temperature of 500 - 600 °C for 8 - 12 h to obtain a third product;
[0071] (4) Mixing the third product and a second coating agent and performing a third sintering in a protective atmosphere at a sintering temperature of 300 - 400 °C for 6 - 8 h to obtain the high-nickel positive electrode active material.
[0072] Specifically, in step (1), the high-nickel positive electrode material precursor with the chemical composition Ni x Co y Mn z (OH)2 is calcined at 400 - 600 °C for 1 - 5 h to obtain a calcined product, where 0.90 ≤ x ≤ 0.98 and x + y + z = 1; the calcined product is respectively ground and crushed to obtain a first product with a median particle size D50 < 0.8 μm. In this process, pre-calcining, grinding, and crushing the high-nickel positive electrode material precursor helps to generate high-nickel positive electrode active materials with small particle sizes, effectively improving the capacity of the positive electrode active material.
[0073] The present invention does not specifically limit the source of the high-nickel cathode material precursor. For example, commercially available products well-known to those skilled in the art or products prepared by conventional preparation methods can be used, as long as the chemical composition of the high-nickel cathode material precursor satisfies Ni x Co y Mn z (OH)2.
[0074] The present invention does not specifically limit the grinding method and the crushing method. Exemplarily, grinding can be performed by at least one of a mechanical pulverizer, a universal pulverizer, and a vacuum ball mill, and crushing can be performed by at least one of a jet mill and a universal pulverizer, as long as the median particle size D50 of the first product is <0.8 μm.
[0075] In step (2), the first product, a lithium source, and a dopant are mixed to obtain a first mixed raw material. Among them, the molar ratio of lithium in the lithium source to the first product is 0.95 to 1.05, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is (0.1 to 10):1000; the first mixed raw material is subjected to a first sintering in an oxygen atmosphere, the sintering temperature is 600 to 850 °C, and the sintering time is 15 to 20 h to obtain a sintered product, which is cooled, crushed, and sieved through a sieve to obtain a second product.
[0076] The theoretical generated mass of 1 mol of the high-nickel cathode active material in the present invention is calculated by formula 5:
[0077] The theoretical generated mass (g) of 1 mol of the high-nickel cathode active material = a×M1 + b×M2 + m×M3 + n×M4 + 2×M5 Formula 5
[0078] In formula 5, M1 is the relative atomic mass of lithium, M2 is the relative atomic mass of nickel, M3 is the relative atomic mass of manganese, M4 is the relative atomic mass of cobalt, and M5 is the relative atomic mass of oxygen.
[0079] The lithium source in the present invention refers to a raw material that provides lithium element, and the dopant refers to a compound including at least two of Zr, Ti, W, B, Sn, Ta, and Ce. As long as it contains the target element, it belongs to the limitation of the present invention. Exemplarily, the lithium source can be selected from at least one of lithium carbonate, lithium sulfate, lithium nitrate, and lithium hydroxide, and the dopant includes at least two of cerium fluoride, tantalum oxide, zirconium oxide, titanium oxide, tungsten oxide, boron oxide, and tin oxide.
[0080] The present invention does not specifically limit the cooling method, the crushing method, and the mesh number of the sieve. Exemplarily, the cooling method can be any one of natural cooling and circulating water cooling, the crushing method can be at least one of a mechanical pulverizer and a jet mill, and the mesh number of the sieve can be selected from any one of 400, 350, and 325.
[0081] During the first sintering process, X (at least two of Zr, Ti, W, B, Sn, Ta, Ce) in the dopant will replace part of Ni, Co, Mn to combine with O, forming X-O bonds with greater bond energy, which can inhibit the overflow of unstable lattice oxygen, improve the cycling performance, and at the same time can also inhibit the growth of primary particles, effectively increasing the specific surface area and powder compaction density of the cathode active material.
[0082] In step (3), the second product is mixed with the first coating agent and subjected to second sintering in an oxygen atmosphere at a sintering temperature of 500-600 °C and a sintering time of 8-12 h to obtain a sintered product, which is cooled, crushed, and sieved to obtain a third product.
[0083] The first coating agent in the present invention refers to a compound including at least one of Zr, Ti, W, B, Sn, Ta, Al, Mo, Co. As long as it contains the target element, it belongs to the definition of the present invention. Exemplarily, the first coating agent includes at least one of tin oxide, titanium oxide, tungsten oxide, tantalum oxide, molybdenum oxide, zirconium oxide, boron oxide, aluminum oxide, cobalt oxide.
[0084] The present invention does not specifically limit the molar ratio between the second product and the first coating agent. When there are two or more first coating agents, the present invention does not specifically limit the molar ratio between the first coating agents, as long as the chemical composition of the prepared high-nickel cathode active material satisfies formula 1.
[0085] The present invention does not specifically limit the methods of cooling, crushing, and sieving. For example, it is consistent with the above definition and will not be elaborated here.
[0086] During the second sintering process, the first coating agent reacts with LiOH and LiCO3 on the surface of the first core layer to generate metal lithium compounds, forming a second core layer on the surface of the first core layer, which helps to reduce the nickel-lithium mixing ratio and make c / a and I (003) / I (104) within the above-defined range, ensuring a high capacity and initial efficiency.
[0087] In step (4), the third product is mixed with the second coating agent and subjected to third sintering in an oxygen atmosphere at a sintering temperature of 300-400 °C and a sintering time of 6-8 h to obtain a sintered product, which is cooled, crushed, and sieved through a sieve to obtain a high-nickel cathode active material.
[0088] The second coating agent in the present invention refers to a compound including at least one of W, Al, B, Co. Exemplarily, the second coating agent includes at least one of boric acid, boron oxide, aluminum oxide, tungsten oxide, cobalt oxide.
[0089] The present invention does not specifically limit the molar ratio between the third product and the second coating agent. When there are two or more second coating agents, the present invention does not specifically limit the molar ratio between the second coating agents, and it is only necessary to make the chemical composition of the prepared high-nickel cathode active material satisfy Formula 1.
[0090] During the third sintering process, the second coating agent is in a molten state at 300-400°C, and can bring the unreacted first coating agent in the second sintering process to the blank part on the surface of the first core layer, so that the first coating agent continues to react with the unreacted LiOH and LiCO3 in the blank part to form a more uniform second core layer; at the same time, the second coating agent also reacts with the unreacted LiOH and LiCO3 in the blank part on the surface of the first core layer to form a uniform coating layer.
[0091] The preparation method of the high-nickel cathode active material of the present invention is to pre-calcine, crush and grind the high-nickel cathode material precursor, and then add a dopant, a first coating agent and a second coating agent respectively during the first sintering, second sintering and third sintering processes. At the same time, by controlling the preparation process parameters, the finally prepared high-nickel cathode active material has the chemical composition of Formula 1, and has a low lithium-nickel mixing ratio, a high c / a value and an I (003) / I (104) value, so as to have a stable layered structure, so that the lithium-ion battery including the high-nickel cathode active material has a high capacity and a high first Coulomb efficiency.
[0092] In addition, through the above preparation method, the content of residual lithium (LiOH and LiCO3) on the surface of the high-nickel cathode active material can be reduced, avoiding the high alkalinity of the material caused by residual lithium, and further causing the formation of jelly-like gel during the preparation of the slurry, which affects the processing performance of the material; at the same time, the occurrence of side reactions between residual lithium and the electrolyte can be avoided, improving the cycle performance and capacity of the battery.
[0093] In a specific embodiment, the first mixed raw material further includes a fluorine source; the mass ratio of the fluorine source to the theoretical generated mass of the high-nickel cathode active material is (1-10):10000. When a fluorine source is added to the first mixed raw material, F in the fluorine source can replace part of O in the first core layer to form F-Ni bonds, F-Co bonds, and F-Mn bonds with higher bond energy, which can not only reduce the content of unstable lattice oxygen in the first core layer, but also inhibit the dissolution of metal ions Ni, Co, and Mn, effectively improving the capacity and life of the battery; when the mass ratio of the fluorine source to the theoretical generated mass of the high-nickel cathode active material is within the above range, the content of unstable lattice oxygen can be further reduced, and the inhibitory effect on the dissolution of metal ions Ni, Co, and Mn can be improved, making the lithium-ion battery have higher capacity and cycle performance.
[0094] In a specific embodiment, the heating rate during the first sintering process is 1 - 4 °C / min. Within this range, it is beneficial to reduce the lithium-nickel mixing rate, such that the lithium-nickel mixing rate of the cathode active material is between 0.009 and 0.015, thereby improving the initial efficiency and capacity of the cathode active material.
[0095] In a specific embodiment, the heating rate during the second sintering process is 1 - 3 °C / min. Within this range, it is beneficial to reduce the lithium-nickel mixing rate and control the morphology of the single-crystal cathode active material, such that the cathode active material has a high capacity.
[0096] In a specific embodiment, the heating rate during the third sintering process is 1 - 3 °C / min. Within this range, the lithium-nickel mixing rate can be further reduced and the morphology of the pseudo single-crystal cathode active material can be controlled, thereby further improving the capacity of the cathode active material.
[0097] The third aspect of the present invention provides a cathode sheet. Since the cathode sheet includes the high-nickel cathode active material of the first aspect above or includes the high-nickel cathode active material prepared by the preparation method of the high-nickel cathode active material of the second aspect above, when the cathode sheet is applied to a lithium-ion battery, the initial Coulombic efficiency and capacity of the battery can be effectively improved.
[0098] The fourth aspect of the present invention provides a lithium-ion battery. Since the lithium-ion battery includes the high-nickel cathode active material of the first aspect above or includes the high-nickel cathode active material prepared by the preparation method of the high-nickel cathode active material of the second aspect above or the cathode sheet of the third aspect above, the battery has a high initial Coulombic efficiency and capacity.
[0099] Hereinafter, the high-nickel cathode active material of the present invention will be introduced in detail through specific examples.
[0100] Example 1
[0101] (1) Calcine the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain a first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0102] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide, and 1.02 g of titanium dioxide uniformly in a high-speed mixer to obtain a first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 4.08:1000. Raise the temperature from room temperature to 725 °C at 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and perform crushing and sieving after natural cooling to obtain a second product;
[0103] (3) Mix 3 kg of the second product with 9.5 g of cobalt hydroxyoxide evenly in a high-speed mixer, raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, naturally cool and then crush and screen to obtain the third product;
[0104] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, naturally cool, crush and screen to obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0105] Example 2
[0106] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.5 μm through mechanical crushing;
[0107] (2) Mix 3 kg of the first product with lithium hydroxide, 3 g of tin oxide and 2 g of tantalum oxide evenly in a high-speed mixer to obtain a first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 1.58:1000. Raise the temperature from room temperature to 725 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, naturally cool and then crush and screen to obtain the second product;
[0108] (3) Mix 3 kg of the second product with 9.5 g of cobalt hydroxyoxide evenly in a high-speed mixer, raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, naturally cool and then crush and screen to obtain the third product;
[0109] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Sn 0.0006 Ta 0.0003 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Sn 0.0006 Ta 0.0003 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0110] Example 3
[0111] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.7 μm through mechanical crushing;
[0112] (2) Mix 3 kg of the first product with lithium hydroxide, 2 g of boron oxide and 2 g of cerium fluoride evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 1.26:1000, and the mass ratio of the fluorine source to the theoretically generated mass of the high-nickel cathode active material is 6.31:10000; Raise the temperature from room temperature to 725 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0113] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0114] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min, carry out heat preservation and sintering for 8 h, conduct the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Ce 0.0003 B 0.01 F 0.0009 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Ce 0.0003 B 0.002 F 0.0009 O2, the chemical composition of the second core layer is LiCoO2, the chemical composition of the coating layer is LiBO2, and the mass percentage content of the F element in the first core layer is 0.017 wt%.
[0115] Example 4
[0116] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.66 μm through mechanical crushing;
[0117] (2) Mix 3 kg of the first product with lithium hydroxide, 1 g of aluminum fluoride and 2 g of tantalum oxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 0.95:1000, and the mass ratio of the fluorine source to the theoretically generated mass of the high-nickel cathode active material is 3.15:10000; Under an oxygen atmosphere, raise the temperature from room temperature to 725 °C at a rate of 2 °C / min, carry out heat preservation and sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0118] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 600 °C at a rate of 2 °C / min, carry out heat preservation and sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0119] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min, carry out heat preservation sintering for 8 h, conduct the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling and crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Al 0.0003 Ta 0.0003 F 0.0009 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Al 0.0003 Ta 0.0003 F 0.0009 O2, the chemical composition of the second core layer is LiCoO2, the chemical composition of the coating layer is LiBO2, and the mass percentage content of F element in the first core layer is 0.017 wt%.
[0120] Example 5
[0121] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0122] (2) Mix 3 kg of the first product with lithium hydroxide, 6.1 g of zirconium oxide, 3.81 g of yttrium oxide, and 2.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 3.76:1000. Under an oxygen atmosphere, raise the temperature from room temperature to 725 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0123] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 600 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0124] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.001 Ti 0.0008 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.001 Ti 0.0008 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0125] Example 6
[0126] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0127] (2) Mix 3 kg of the first product with lithium hydroxide, 7.6 g of zirconium oxide, 4.81 g of yttrium oxide and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 4.24:1000. Under an oxygen atmosphere, raise the temperature from room temperature to 725 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0128] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 600 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0129] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min, carry out heat preservation sintering for 8 h, conduct the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.002 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.002 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0130] Example 7
[0131] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0132] (2) Mix 3 kg of the first product with lithium hydroxide, 6.8 g of zirconium oxide, 3.21 g of yttrium oxide and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 3.48:1000. Under an oxygen atmosphere, raise the temperature from room temperature to 725 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0133] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 600 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0134] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 8 h, conduct the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling and crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0135] Example 8
[0136] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0137] (2) Mix 3 kg of the first product with lithium hydroxide, 7.2 g of zirconium oxide, 2.81 g of yttrium oxide and 0.86 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 3.43:1000. Raise the temperature from room temperature to 725 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0138] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0139] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, hold for heat preservation and sinter for 8 h, conduct the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling and crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0003 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0003 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0140] Example 9
[0141] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0142] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide, 2 g of cerium fluoride and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 4.71:1000, and the mass ratio of the fluorine source to the theoretically generated mass of the high-nickel cathode active material is 6.31:10000; Raise the temperature from room temperature to 725 °C at a rate of 2 °C / min under an oxygen atmosphere, hold for heat preservation and sinter for 10 h, and after natural cooling, conduct crushing and sieving to obtain the second product;
[0143] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, hold for heat preservation and sinter for 10 h, and after natural cooling, conduct crushing and sieving to obtain the third product;
[0144] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min, carry out heat preservation sintering for 8 h, conduct the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 Ce 0.0003 F 0.0009 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 Ce 0.0003 F 0.0009 O2, the chemical composition of the second core layer is LiCoO2, the chemical composition of the coating layer is LiBO2, and the mass percentage content of F element in the first core layer is 0.017 wt%.
[0145] Example 10
[0146] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0147] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide, 10 g of cerium fluoride and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 7.23:1000, and the mass ratio of the fluorine source to the theoretically generated mass of the high-nickel cathode active material is 31.54:10000; Under an oxygen atmosphere, raise the temperature from room temperature to 725 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0148] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, naturally cool and then crush and screen to obtain the third product;
[0149] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and screening, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 Ce 0.001 F 0.003 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y[[ID=3�]] 0.001 Ce 0.001 F 0.003 O2, the chemical composition of the second core layer is LiCoO2, the chemical composition of the coating layer is LiBO2, and the mass percentage content of F element in the first core layer is 0.058 wt%.
[0150] Example 11
[0151] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0152] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain a first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 4.08:1000. Raise the temperature from room temperature to 700 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, naturally cool and then crush and screen to obtain the second product;
[0153] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, cool naturally, and then crush and screen to obtain the third product;
[0154] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, cool naturally, crush and screen, and then obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0155] Example 12
[0156] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0157] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide, and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain a first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 4.08:1000. Raise the temperature from room temperature to 825 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, cool naturally, and then crush and screen to obtain the second product;
[0158] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, cool naturally, and then crush and screen to obtain the third product;
[0159] (4) 3 kg of the third product and 17.1 g of boric acid were mixed evenly in a high-speed mixer, and the temperature was raised from room temperature to 330 ° C at 2 ° C / min in an oxygen atmosphere, and the heat preservation sintering was carried out for 8 hours. The third sintering was carried out in an oxygen atmosphere to obtain a sintered product, which was naturally cooled, crushed and sieved to obtain the high-nickel positive electrode active material of this embodiment. The chemical composition of the positive electrode active material was Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first inner core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second inner core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0160] Example 13
[0161] (1) Ni 0.96 Co 0.03 Mn 0.01 (OH)2 was calcined at 500 °C for 5 h and mechanically crushed to obtain the first product with a median particle size D50 of 0.6 μm;
[0162] (2) 3 kg of the first product was mixed with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide and 1.02 g of titanium dioxide in a high-speed mixer to obtain a first mixed material, wherein the molar ratio of the lithium source to the first product was 1.04, and the mass ratio of the dopant to the theoretical mass of the high-nickel positive electrode active material was 4.08:1000. The temperature was raised from room temperature to 850°C at a rate of 2°C / min in an oxygen atmosphere, and the mixture was kept warm and sintered for 10 hours. After natural cooling, the mixture was crushed and sieved to obtain a second product.
[0163] (3) 3 kg of the second product and 9.5 g of cobalt oxyhydroxide were mixed uniformly in a high-speed mixer, and the temperature was raised from room temperature to 600° C. at a rate of 2° C. / min in an oxygen atmosphere, and the mixture was kept warm and sintered for 10 h. After natural cooling, the mixture was crushed and sieved to obtain a third product;
[0164] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min, carry out heat preservation sintering for 8 h, conduct the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0165] Example 14
[0166] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0167] (2) Mix evenly 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide, 4 g of cerium fluoride and 1.02 g of titanium dioxide in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 5.34:1000, and the mass ratio of the fluorine source to the theoretically generated mass of the high-nickel cathode active material is 1,261:10,000; under an oxygen atmosphere, raise the temperature from room temperature to 725 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0168] (3) Mix evenly 3 kg of the second product with 9.5 g of cobalt oxyhydroxide in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 600 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0169] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 Ce 0.0005 F 0.0015 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 Ce 0.0005 F 0.0015 O2, the chemical composition of the second core layer is LiCoO2, the chemical composition of the coating layer is LiBO2, and the mass percentage content of F element in the first core layer is 0.02 wt%.
[0170] Example 15
[0171] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0172] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 4.08:1000. Raise the temperature from room temperature to 725 °C at a rate of 7 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0173] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0174] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 330 °C at a rate of 2 °C / min, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0175] Example 16
[0176] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0177] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 4.08:1000. Under an oxygen atmosphere, raise the temperature from room temperature to 725 °C at a rate of 2 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0178] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Under an oxygen atmosphere, raise the temperature from room temperature to 600 °C at a rate of 8 °C / min, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0179] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer. Raise the temperature from room temperature to 330 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 8 h, carry out the third sintering under an oxygen atmosphere to obtain a sintered product, and after natural cooling, crushing and sieving, obtain the high-nickel cathode active material of this example. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0180] Example 17
[0181] (1) Calcinate the high-nickel cathode material precursor Ni 0.96 Co 0.03 Mn 0.01 (OH)2 at 500 °C for 5 h, and obtain the first product with a median particle size D50 of 0.6 μm through mechanical crushing;
[0182] (2) Mix 3 kg of the first product with lithium hydroxide, 8.1 g of zirconium oxide, 3.81 g of yttrium oxide and 1.02 g of titanium dioxide evenly in a high-speed mixer to obtain the first mixed material. Among them, the molar ratio of the lithium source to the first product is 1.04, and the mass ratio of the dopant to the theoretical generated mass of the high-nickel cathode active material is 4.08:1000. Raise the temperature from room temperature to 725 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the second product;
[0183] (3) Mix 3 kg of the second product with 9.5 g of cobalt oxyhydroxide evenly in a high-speed mixer. Raise the temperature from room temperature to 600 °C at a rate of 2 °C / min under an oxygen atmosphere, carry out heat preservation sintering for 10 h, and after natural cooling, carry out crushing and sieving to obtain the third product;
[0184] (4) Mix 3 kg of the third product with 17.1 g of boric acid evenly in a high-speed mixer, and raise the temperature from room temperature to 330 °C at a rate of 9 °C / min under an oxygen atmosphere, then carry out heat preservation sintering for 8 h, and carry out the third sintering under an oxygen atmosphere to obtain a sintered product. After natural cooling, crushing and sieving, the high-nickel cathode active material of this example is obtained. After ICP detection, the chemical composition of this cathode active material is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0004 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0185] Comparative Example 1
[0186] The preparation method of the high-nickel cathode active material in this comparative example is basically the same as that in Example 1, the difference is that in step (1), the sintering temperature is 650 °C and the heat preservation sintering time is 6 h.
[0187] After ICP detection, the chemical composition of the high-nickel cathode active material prepared in this comparative example is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0005 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.0 1Zr 0.002 Ti 0.0005 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0188] Comparative Example 2
[0189] The preparation method of the high-nickel cathode active material in this comparative example is basically the same as that in Example 1, the difference is that in step (1), the median particle size of the first product is 1.1 μm.
[0190] By ICP detection, the chemical composition of the high-nickel cathode active material prepared in this comparative example is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0005 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.0 1Zr 0.002 Ti 0.0005 Y 0.001 O2, the chemical composition of the second core layer is LiNiO2, and the chemical composition of the coating layer is LiBO2.
[0191] Comparative Example 3
[0192] The preparation method of the high-nickel cathode active material in this comparative example is basically the same as that in Example 1, except that in step (2), the sintering temperature is 580 °C and the sintering time is 13 h.
[0193] By ICP detection, the chemical composition of the high-nickel cathode active material prepared in this comparative example is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0005 Y 0.001 B 0.008 O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.00 2Ti 0.0005 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0194] Comparative Example 4
[0195] The preparation method of the high-nickel cathode active material in this comparative example is basically the same as that in Example 1, except that in step (2), the addition amount of the dopant zirconia is 22.37 g, the addition amount of yttrium oxide is 10.12 g, the addition amount of titanium dioxide is 5.54 g, and the mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is 12:1000.
[0196] By ICP detection, the chemical composition of the high-nickel cathode active material prepared in this comparative example is Li 1.04 Ni0.96 Co 0.03 Mn 0.01 Zr 0.005 Ti 0.002 Y 0.003 B 0.008 O₂, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.005 Ti 0.002 Y 0.003 O₂, the chemical composition of the second core layer is LiCoO₂, and the chemical composition of the coating layer is LiBO₂.
[0197] Comparative Example 5
[0198] The preparation method of the high-nickel cathode active material in this comparative example is basically the same as that in Example 1, except that in step (3), the sintering temperature is 400 °C and the holding sintering time is 5 h.
[0199] Detected by ICP, the chemical composition of the high-nickel cathode active material prepared in this comparative example is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0005 Y 0.001 B 0.008 O₂, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.0 1Zr 0.002 Ti 0.0005 Y 0.001 O₂, the chemical composition of the second core layer is LiCoO₂, and the chemical composition of the coating layer is LiBO₂.
[0200] Comparative Example 6
[0201] The preparation method of the high-nickel cathode active material in this comparative example is basically the same as that in Example 1, except that in step (4), the sintering temperature is 500 °C and the holding sintering time is 15 h.
[0202] Detected by ICP, the chemical composition of the high-nickel cathode active material prepared in this comparative example is Li 1.04 Ni 0.96 Co 0.03 Mn 0.01 Zr 0.002 Ti 0.0005 Y 0.001 B 0.008O2, where the chemical composition of the first core layer is Li 1.04 Ni 0.96 Co 0.03 Mn 0.0 1Zr 0.002 Ti 0.0005 Y 0.001 O2, the chemical composition of the second core layer is LiCoO2, and the chemical composition of the coating layer is LiBO2.
[0203] Test Examples
[0204] 1. Perform SEM tests on the high-nickel cathode active materials prepared in Examples 1-4 above. The test results are as Figures 1-4 shown; perform XRD tests on the high-nickel cathode active materials prepared in the above examples and comparative examples. The test results are shown in Table 1; perform ICP tests on the high-nickel cathode active materials prepared in the above examples and comparative examples to obtain the molar amount of Li / (Ni + Co + Mn); perform physical and chemical property tests on the high-nickel cathode active materials prepared in the above examples and comparative examples to obtain the primary particles and D50, specific surface area, and powder compaction density of the high-nickel cathode active materials. The test results are shown in Table 1.
[0205] Figures 1-4 are SEM images of the high-nickel cathode active materials prepared in Example 1, Example 2, Example 3, and Example 4 respectively. As Figures 1-4 can be seen, the prepared high-nickel cathode active materials have a smaller particle size and a rough surface, which helps to improve the specific capacity of the cathode active materials.
[0206] 2. Apply the high-nickel cathode active materials prepared in the above examples and comparative examples to lithium-ion batteries. The specific steps are as follows:
[0207] Mix and stir the high-nickel cathode active materials prepared in the above examples and comparative examples with conductive carbon, polyvinylidene fluoride, and N-methylpyrrolidone in a mass ratio of 85:10:5 to ensure a fineness of 10 μm and a viscosity of 5000 mPa·s to obtain the cathode active layer slurry; after passing the cathode active layer slurry through a 200-mesh sieve, coat it on the surface of the cathode current collector aluminum foil. The surface density of the coating is 370 g / m 2 , dry it at 120 °C for 80 min, roll and slice it to obtain the cathode sheet, where the compaction density is 3.45 g / cm 3 ; assemble the cathode sheet with a lithium sheet, a cellulose separator, and a conventional lithium hexafluorophosphate electrolyte into a button cell. Among them, the electrolyte includes ethylene carbonate, ethyl methyl carbonate, and lithium hexafluorophosphate. The volume ratio of ethylene carbonate and ethyl methyl carbonate (EMC) is 3:7, and the mass percentage content of lithium hexafluorophosphate is 12.5 wt%.
[0208] The button cells including the high nickel positive active materials of the above examples and comparative examples were tested for capacity and initial coulombic efficiency:
[0209] (1) Capacity
[0210] Charge at a constant current rate of 0.2C to a voltage of 4.25V, then charge at a constant voltage under the cut-off voltage condition until the current is less than 0.05C. The charging capacity at this time is recorded as the first-cycle charging capacity. After that, let it stand for 5 minutes, and then discharge at a constant current rate of 0.2C to a voltage of 2.5V. The discharge capacity this time is recorded as the first-cycle discharge capacity of the battery, which is the initial capacity.
[0211] The test results are shown in Table 2.
[0212] (2) First Coulombic efficiency
[0213] At 25°C, the charge and discharge voltage window is 2.5-4.3V. Charge at 0.2C and discharge at 0.2C, and obtain the 0.2C discharge gram capacity C1 and the 0.2C charge gram capacity C2. The first coulombic efficiency is calculated by formula 5.
[0214] First coulombic efficiency (%) = C1 / C2 Formula 5
[0215] The test results are shown in Table 2.
[0216] (3) Residual lithium test
[0217] 30 g of the high-nickel positive electrode material prepared in the above embodiment and comparative example were weighed separately for standby use, the weighed sample was placed in a 100 mL beaker, 50 mL of deionized water was added, and the magnetic beads were placed in the beaker and sealed with plastic wrap. The beaker was placed on a magnetic stirrer and stirred for about 25 minutes before removal; it was allowed to stand for 5 minutes and filtered using a glass funnel. The filtered clear liquid was the test solution; the content of residual alkali (Li2CO3 and LiOH) in the test solution was tested by an automatic potentiometric titrator. The titrant was 0.1 M HCl and the titration rate was 0.5 mL / min. The endpoints V1 and V2 were obtained, and the contents of LiOH and Li2CO3 were calculated by Equations 6 and 7:
[0218] Li2CO3(ppm)=0.001×73.89 / (V2-V1) Equation 6
[0219] LiOH(ppm)=0.001×23.95 / (2V1-V2) Equation 7
[0220] The calculation results are shown in Table 2.
[0221] Table 1
[0222]
[0223]
[0224] Table 2
[0225]
[0226]
[0227] As can be seen from Table 1 and Table 2:
[0228] Compared with the cathode active materials of Comparative Examples 1 - 6, the lithium-nickel mixing ratio of the cathode active materials in Examples 1 - 17 is lower, and c / a and I(003) / I(104) are higher. Therefore, when the cathode active materials in Examples 1 - 17 are applied to the battery, the capacity and initial Coulombic efficiency of the battery can be significantly improved. The 0.2C charge specific capacity of the batteries in Examples 1 - 17 can reach up to 252.7 mAh / g at most, the 0.2C discharge specific capacity can reach up to 239.1 mAh / g at most, and the initial Coulombic efficiency can reach up to 96.91% at most, which is significantly higher than that of Comparative Examples 1 - 6. Thus, it can be known that the cathode active material of the present invention can significantly improve the capacity and initial Coulombic efficiency of the battery.
[0229] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that: they can still modify the technical solutions recorded in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-nickel cathode active material, characterized in that, Comprising the chemical composition shown in Formula 1, Li a Ni b Mn m Co n X c O2 Formula 1 In Formula 1, 0.95 ≤ a ≤ 1.05, 0.90 ≤ b ≤ 0.98, 0 < c ≤ 0.016, b + m + n = 1, and X comprises at least two of Zr, Ti, W, B, Sn, Ta, Al, Mo, Co, Ce; The lithium-nickel mixing ratio of the high-nickel cathode active material is 0.009 to 0.015; In the X-ray diffraction pattern of the high-nickel cathode active material, c / a is 4.8 to 5.2; c / a refers to the ratio of the lattice constant c of the c-axis to the lattice constant a of the a-axis; In the X-ray diffraction pattern of the high-nickel cathode active material, the peak areas of the diffraction peaks at 2θ of 18.8 ± 0.5° and 44.3 ± 0.5° are I (003) , I (104) , respectively, and I (003) / I (104) is 1.8 to 2.4; The high-nickel cathode active material comprises a core layer and a coating layer covering at least part of the surface of the core layer; the core layer comprises a first core layer and a second core layer covering at least part of the surface of the first core layer; the first core layer has the chemical composition of Formula 2, the second core layer has the chemical composition of Formula 3, and the coating layer has the chemical composition of Formula 4, Li d Ni e Mn f Co g X 1 h O2 formula 2 LiX 2 O2 formula 3 LiX 3 O2 formula 4 In Formula 2, 0.95 ≤ d < 1.05, 0.9 ≤ e ≤ 0.98, e + f + g = 1, 0 < h < 0.016, X 1 comprises at least two of Zr, Ti, W, B, Sn, Ta, and Ce; In Formula 3, X 2 includes at least one of Zr, Ti, W, B, Sn, Ta, Al, Mo, and Co; In Formula 4, X 3 includes at least one of W, Al, B, and Co.
2. The high-nickel cathode active material according to claim 1, wherein The first core layer further comprises F element; the mass percentage content of F element in the first core layer is 0.01 to 0.045 wt%; 3. The high-nickel cathode active material according to claim 1 or 2, characterized in that, The high-nickel cathode active material comprises secondary particles composed of primary particles; The median particle size of the primary particles is 0.2 to 1 μm, and / or the median particle size of the high-nickel cathode active material is 0.7 to 1.5 μm.
4. The high-nickel cathode active material according to claim 1 or 2, wherein The specific surface area of the high-nickel cathode active material is 0.9 to 5 m 2 / g, and / or the powder tap density of the high-nickel cathode active material is 3.1 to 3.4 g / cm 3 .
5. A method for preparing the high-nickel cathode active material according to any one of claims 1-4, characterized in that, Comprising the following steps: (1) Calcinate the high-nickel cathode material precursor Ni x Co y Mn z (OH)2 at 400-600 °C for 1-5 h, and obtain the first product with a median particle size D50 < 0.8 μm after grinding and crushing, where 0.90 ≤ x ≤ 0.98 and x + y + z = 1; (2) Mix the first product, a lithium source, and a dopant to obtain a first mixed raw material, and perform a first sintering in an oxygen atmosphere at a sintering temperature of 600 to 850 °C and a sintering time of 15 to 20 h to obtain a second product; The molar ratio of lithium in the lithium source to the first product is 0.95 to 1.05; The mass ratio of the dopant to the theoretically generated mass of the high-nickel cathode active material is (0.1 to 10):1000; (3) Mix the second product and a first coating agent and perform a second sintering in an oxygen atmosphere at a sintering temperature of 500 to 600 °C and a sintering time of 8 to 12 h to obtain a third product; (4) Mix the third product and a second coating agent and perform a third sintering in a protective atmosphere at a sintering temperature of 300 to 400 °C and a sintering time of 6 to 8 h to obtain the high-nickel cathode active material; The heating rate in the first sintering process is 1 to 4 °C / min, and / or the heating rate in the second sintering process is 1 to 3 °C / min, and / or the heating rate in the third sintering process is 1 to 3 °C / min.
6. The preparation method of the high-nickel cathode active material according to claim 5, wherein The first mixed raw material further comprises a fluorine source; The mass ratio of the fluorine source to the theoretically generated mass of the high-nickel cathode active material is (1 to 10):10000.
7. A positive electrode sheet, characterized in that, Comprising the high-nickel cathode active material according to any one of claims 1-4 or the high-nickel cathode active material prepared by the preparation method of the high-nickel cathode active material according to claim 5 or 6.
8. A lithium-ion battery, characterized in that, Comprising the high-nickel cathode active material according to any one of claims 1-4 or the high-nickel cathode active material prepared by the preparation method of the high-nickel cathode active material according to any one of claims 5 or 6 or the positive electrode sheet according to claim 7.
Citation Information
Patent Citations
A co-doped modified high-nickel ternary material and a preparation method thereof
CN109119628A